Applied Cryptography and Network Security 7th International Conference, ACNS 2009, Paris-Rocquencourt, France, June 2-5, 2009, Proceedings - Abdalla, Michel; Pointcheval, David; Fouque, Pierre-Alain; Vergnaud, Damien (Security and Cryptology ;, 2009)
This book constitutes the refereed proceedings of the 7th International Conference on Applied Cryptography and Network Security, ACNS 2009, held in Paris-Rocquencourt, France, in June 2009. The 32 revised full papers presented were carefully reviewed and selected from 150 submissions. The papers are organized in topical sections on key exchange, secure computation, public-key encryption, network security, traitor tracing, authentication and anonymity, hash fundtions, lattices, and side-channel attacks.